Sacred and secular intersections in music of the long Nineteenth Century church, stage, and Concert Hall - Papanikolaou, Eftychia 1968-; Rathey, Markus 1968- (Lexington Books, 2022)
The book explores interconnections of the sacred and the secular in music of the long nineteenth century. It investigates manifestations of religion in music not primarily intended for liturgical performance and assesses compositions that originated in a liturgical context but then migrated in their performance into a non-liturgical sphere.